2020
DOI: 10.1111/1541-4337.12690
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial spores in spices and dried herbs: The risks for processed food

Abstract: Production and world consumption of spices are constantly increasing. Although the antimicrobial properties of some spices are well documented, their use in the agri‐food industry is also responsible for microbial contamination and spoilage. Bacterial spores introduced by spices can withstand different preparation processes, particularly thermal treatments, leading to food alterations during storage. This review brings together data from the literature about the prevalence and concentrations of spore‐forming b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 93 publications
(300 reference statements)
0
30
0
1
Order By: Relevance
“…High temperatures in evaporators (operated under vacuum) in combination with a low Aw in the concentrated product stream put selective pressures that favor outgrowth and subsequent spore formation by B. licheniformis (Burgess et al, 2010;Eijlander et al, 2019;Delaunay et al, 2021). Besides dairy products, the organism is also frequently found in spices, dry herbs (e.g., pepper and turmeric) (Mathot et al, 2021), and flours (Rosenkvist and Hansen, 1995;Iurlina et al, 2006). As a common contaminant in food ingredients, the processing conditions will determine whether viable spores are present in the finished product (Postollec et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…High temperatures in evaporators (operated under vacuum) in combination with a low Aw in the concentrated product stream put selective pressures that favor outgrowth and subsequent spore formation by B. licheniformis (Burgess et al, 2010;Eijlander et al, 2019;Delaunay et al, 2021). Besides dairy products, the organism is also frequently found in spices, dry herbs (e.g., pepper and turmeric) (Mathot et al, 2021), and flours (Rosenkvist and Hansen, 1995;Iurlina et al, 2006). As a common contaminant in food ingredients, the processing conditions will determine whether viable spores are present in the finished product (Postollec et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2, the share of notifications questioning the microbiological status of herbs and spices is significant. It is postulated that one of the reasons for the low microbiological quality is non-compliance with the principles of good hygienic practice after harvesting the raw material, especially during the drying process of herbs and spices [60,61]. Hence, the solution to this problem is seen in new, innovative methods of preserving the raw material for the production of spices [62].…”
Section: Product Innovations In the Group Of Spices And Seasoning Mixesmentioning
confidence: 99%
“…While KR product is a homogenous thick liquid, consisting mainly from tomato paste and water, KGH product contains dried spices in relatively large amounts (Table 1). Since spices are generally considered as a heat stable spore-forming bacteria contaminant [19], it is fair to suggest that KGH TPC results should be less homogenous in comparison with the KR TPC results. Statistical data analysis showed that there is no significant statistical difference (p > 0.05) between product types or filling temperature effectiveness.…”
Section: Product Microbial Analysismentioning
confidence: 99%